The Impact of Ambidextrous Leadership on Strategic Success: An Analytical Study of the Opinions of a Group of Administrative Leaders and Employees in Al-Waha Company - jasim, Sara thamer (Journal of Ecohumanism, 2025)
This study aimed to identify the nature of the relationship between excellent leadership and strategic success based on the main idea that excellent leadership is the cornerstone of achieving strategic success. To achieve this, the opinions of a number of (department managers, units, and employees) from Al-Waha Company for soft drinks, juices, mineral water, plastics, and limited plastic cap manufacturing in Babil Governorate / Al-Dibla were surveyed. To achieve this goal, a questionnaire was prepared as the main tool for data collection, distributed by the researcher to (100) (employees, department managers, and units). The independent variable (excellent leadership) included two dimensions :(Open Leadership Behaviors, Closed Leadership Behaviors), while the dependent variable (Strategic Success) included three dimensions: (Flexibility, Adaptability, Growth). The number of retrieved questionnaires was 100, with a 100% retrieval rate, and they were analyzed using statistical software program 23.SPSS V). The programs used were (23). Amos) and Microsoft Excel 2010. The results of the statistical analysis showed that the study variables had moderate percentages in AL-Waha Company under study. The analysis results also indicated a positive and significant correlation between the variables under study, as well as a significant direct impact of excellent leadership on strategic success. Therefore, the study recommended, within an intellectual perspective, the importance of managers paying attention to Excellent leadership for its significance in the excellence, success, and distinction of the company.